Effect of hydroalcoholic extract of Cannabis (Cannabis sativa L.) on morphology and the process of human adipose-drived mesenchymal stem cell growth. Issue 3 (June 2018) - Jamshidi, Mehregan; ,; Hosseini, Seyed Ebrahim; Mehrabani, Davood; Amini, Masoud
No abstract available